STUDENTS’ ATTITUDE TOWARDS AMERICAN ACCENT IN COMMUNICATION CONTEXT AT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Isnaeni, Andi; Natsir, Ratu Yulianti; Hambali, Uyunnasirah (Premise: Journal of English Education and Applied Linguistics, 2024)
An accent is one of the aspects of sociolinguistics that discusses how a group of people in each particular region pronounces words. In communication, accent is the color and variety in speech. People often do not pay much attention to this when speaking. This research aims to know the students’ attitudes toward the American accent in the context of communication at Universitas Muhammadiyah Makassar. The method used was mixed, using questionnaires and interviews as the instruments. Twenty students served as samples in this research. Based on cognitive, affective, and conative components, the findings demonstrated that students had a positive attitude towards American accents. In the cognitive component, students tended to believe that speaking with an American accent was easy and enjoyable because they were accustomed to speaking in English daily. Meanwhile, most students expressed interest in speaking with an American accent in the affective component due to its ease of use. In the conative component, the students then seemed to enjoy imitating the way Native American speakers spoke. The implication of this research is in sociolinguistics regarding attitude and intercultural communication related to accents.